"Time is of the essence": relationship between hospital staff perceptions of time, safety attitudes and staff wellbeing - Louise A. Ellis; Yvonne Tran; Chiara Pomare; Janet C. Long; Kate Churruca; Zeyad Mahmoud; Winston Liauw; Jeffrey Braithwaite (BMC, 2021)
Abstract Background Hospitals are perceived as fast-paced and complex environments in which a missed or incorrect diagnosis or misread chart has the potential to lead to patient harm. However, to date, limited attention has been paid to studying how hospital sociotemporal norms may be associated with staff wellbeing or patient safety. The aim of this study was to use novel network analysis, in conjunction with well-established statistical methods, to investigate and untangle the complex interplay of relationships between hospital staff perceived sociotemporal structures, staff safety attitudes and work-related well-being. Method Cross-sectional survey data of hospital staff (n = 314) was collected from four major hospitals in Australia. The survey included subscales from the Organizational Temporality Scale (OTS), two previously established scales of safety attitudes (teamwork climate and safety climate) and measures of staff-related wellbeing (job satisfaction, emotional exhaustion, depersonalisation). Results Using confirmatory factor analysis, we first tested a 19-item version of the OTS for use in future studies of hospital temporality (the OTS-H). Novel psychological network analysis techniques were then employed, which identified that "pace" (the tempo or rate of hospital activity) occupies the central position in understanding the complex relationship between temporality, safety attitudes and staff wellbeing. Using a path analysis approach, serial mediation further identified that pace has an indirect relationship with safety attitudes through wellbeing factors, that is, pace impacts on staff wellbeing, which in turn affects hospital safety attitudes. Conclusions The findings of this study are important in revealing that staff wellbeing and safety attitudes can be significantly improved by placing more focus on temporal norms, and in particular hospital pace. There are implications for increasing levels of trust and providing staff with opportunities to exercise greater levels of control over their work.